2010
DOI: 10.1111/j.1600-0501.2009.01899.x
|View full text |Cite
|
Sign up to set email alerts
|

Prefabricated zirconium dioxide implant abutments for single‐tooth replacement in the posterior region: evaluation of peri‐implant tissues and superstructures after 12 months of function

Abstract: After 12 months of wear, no mechanical failure was registered in any of the all-ceramic abutments. On clinical investigation, the peri-implant hard and soft tissues were largely healthy and devoid of inflammation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
46
1
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(53 citation statements)
references
References 31 publications
4
46
1
2
Order By: Relevance
“…Groten and Huttig [30] reported 2 ceramic veneering material chippings of 54 single crowns after 28 months which needed replacement. Nothdurft and Pospiech [35] showed 10 % and Schwarz et al [36] reported 24.5 % porcelain chipping in Cercon single crowns on implant abutments. In the study conducted by Schwarz et al [36], 11.3 % of fractures led to failure.…”
Section: Discussionmentioning
confidence: 97%
“…Groten and Huttig [30] reported 2 ceramic veneering material chippings of 54 single crowns after 28 months which needed replacement. Nothdurft and Pospiech [35] showed 10 % and Schwarz et al [36] reported 24.5 % porcelain chipping in Cercon single crowns on implant abutments. In the study conducted by Schwarz et al [36], 11.3 % of fractures led to failure.…”
Section: Discussionmentioning
confidence: 97%
“…In addition, subgroup analyses were performed on the selected outcome variables using the type of test abutment material (zirconia, gold, alumina, etc.) After this analysis, 33 final articles were included for data extraction, which represented 29 independent investigations, as in four groups articles, results of the same material were reported at different time points (Andersson, Glauser, Maglione, & Taylor, 2003;Andersson, Scharer, Simion, & Bergstrom, 1999;Brown & Payne, 2011;Nothdurft, Nonhoff, & Pospiech, 2014;Nothdurft & Pospiech, 2010;Tawse-Smith et al, 2017;Zembic, Bosch, Jung, Hammerle, & Sailer, 2013;Zembic, Sailer, Jung, & Hammerle, 2009). For the main outcome, subgroup analyses were performed using the type of study design (CS, CCTs, RCTs [split+parallel], RCTs [split] or RCTs for full-text analysis (agreement = 96.10%; kappa = 0.92; 95% CI [0.83-1.00]; p < 0.001).…”
Section: Data Analysesmentioning
confidence: 99%
“…All the studies were published from 2000-2017. In nineteen studies (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29) the implants were placed by means of a standard surgical protocol in a healed normal implant site of bone Type III or IV. an ‗early' implant placement in two studies (Type II) was performed and immediate implant placement in other three studies (Type I) was done.…”
Section: Results:-mentioning
confidence: 99%
“…In case of absence of single tooth many treatments can restore it such as implant supported single tooth restoration, conventional fixed partial denture or cantilevered fixed partial denture. (25) RCTs are seemed to be of high evidence level to contrast between different treatment patterns. consequently, obscurity of RCTs in comparing these various treatment patterns will lead to depreciation the evidence level.…”
Section: Discussion:-mentioning
confidence: 99%